Assessing students' mathematics achievement and mathematical creativity using mathematical creative approach: a quasi-experimental research / Nor Haniza Abdul Hamid and Nurzatulshima Kamarudin - Abdul Hamid, Nor Haniza; Kamarudin, Nurzatulshima (Universiti Teknologi MARA, 2021)
There is an abundance of literature highlighting the need to focus on enhancing students' creativity in the classroom. This research aimed to determine the impact of the Mathematical Creative Approach (MCA) on mathematical creativity and mathematics achievement among students and to explore the relationship between mathematical creativity and achievement in mathematics. A quasi-experimental research design was employed for the study that included a total of 64 Form Four students from schools in Kuala Lumpur; 32 students in the intervention group and 32 students in the comparison group. The findings showed that those participants who were exposed to MCA reported significant positive changes in both outcome variables (mathematical creativity and mathematics achievement) as compared with those from the control group. Based on the results, there was also a high correlation between mathematical creativity and mathematics achievement. The research revealed that MCA has enormous capabilities to promote creativity; hence it should be integrated into pedagogical approaches to foster higher-quality learning among students. Additionally, the research results may serve as a guide for educators in Higher Learning institutions to design innovative curriculum for pre-service mathematics teachers, especially those being trained to integrate creativity and character development into student learning.